ENHANCING THE ‘SOCIO-ECONOMIC’ TERRITORY OF WESTERN ALGERIA THROUGH TOURISTIC VALORIZATION OF THE RAILWAY HERITAGE: THE CASE OF “SIDI-BELABBÈS / AKKID-ABBES” LINE - Chahineze Slimani; Boussad Aiche (International Journal of Innovative Technologies in Social Science, 2024)
The drive to modernize the Algerian railway system raises the question of the future of the cultural assets connected to the old route. The aim of this article is to explore this issue by looking at the potential effects on the growth of a tourist and economic revitalization project that could result from the establishment of a cultural itinerary along the study line. Utilizing unpublished archival sources and cross-referencing them with field research constitutes the foundation of this study. The identification of railway components consists of a reading grid based on the concept (objective and subjective) of the railway landscape. Universal values and the UNESCO World Heritage selection criteria serve as the basis for its evaluation. The QGIS geographic information system complements the inventory approach. The results of this study reveal a monumental landscape, technical and architectural set of the West Algeria railway line, which elevates it into the category of cultural route which could also offer a new opportunity for economic development for the region through cultural tourism. The Qgis database contributes to the creation of an awareness-raising tool for better asset management.